Effects of Relative Humidity on the Diurnal Variation of Raindrop Size Distribution in Southwest China - Sun, Jing; Wan, Rong; Zhou, Yue (Frontiers in Environmental Science, 2022)
This study assessed the impacts of relative humidity (RH) on diurnal variation in the raindrop size distribution (RSD) within a region in China with a valley topography (Zigui region) from 2019 to 2020 based on a two-dimensional video disdrometer (2DVD), auto-weather station (AWS) data, and ERA5. The daytime RSD structure under an RH < 60% and ≥ 60% showed three peaks and a single peak, respectively. Nighttime RSD under RH ≥ 60% and < 60% showed a single peak and two peaks, respectively. The daytime RSDs of short-duration precipitation Amount(SPA) showed broader distributions than the nighttime RSDs, whereas the nighttime RSDs of long-duration precipitation Amount (LPA) exhibited the opposite trend. Higher ground RH changed the RSD shape by sorting raindrops, collision-coalescence and breakup due to the formation of large raindrops. Under a constant RH, the melting and collision-coalescence of large raindrops in the daytime of SPA exceeded those of LPA. This difference may be related to the near-surface wind filed and the intensity of convection.